(untitled) (SAARC Journal of Agriculture, 2026)
Rice is cultivated worldwide, and using nanoproducts opens a new era in the agricultural system. To evaluate the yield and yield parameters of Boro rice, an experiment was conducted at the Sher-e-Bangla Agricultural University, Dhaka from December 2019 to May 2020 to study the effect of Stalwart Nano Product (SNP2) and Carbendazim on the yield of Boro rice. The experiment considered two rice varieties (BRRI dhan28 and BRRI dhan63) and SNP2 with or without Carbendazim as treatment factors. The study was conducted to minimize the yield gap with the treatment used. Effective tiller number hill-1, filled grain panicle-1, 1000-seed weight (g), grain yield (t ha-1), and straw yield (t ha-1) were selected as parameters. Results revealed that BRRI dhan63 showed better performance than BRRI dhan28 regarding grain yield (6.11 t ha-1) and straw yield. At the individual effect of the application of chemical spray (SNP2 and carbendazim combination), the highest number of effective tiller hill-1, number of filled grain panicle-1 and grain yield (5.74 t ha-1) was recorded from T5 (Carbendazim @ 2g L-1 + SNP2 @ 1.0 ml L-1) treatment. However, in the case of the combined effect, the higher grain yield (6.35 t ha-1) was recorded in BRRI dhan63 treated with T5 treatment. The result revealed that using the nanoproduct and Carbendazim boosted yield compared to the control treatment (T0) in both studied varieties. SAARC J. Agric., 23(2): 1-8 (2025)